The necessary transformation for an inclusive, democratic, and effective State - Bachelet , Michelle (Revista del CLAD Reforma y Democracia, 2025)
When we talk about the necessary transformation of the State, we cannot think in abstract terms. We must consider a State within a global, regional, and specific context.We are facing a triple planetary crisis. We often speak of climate change, but at the United Nations, we talk not only about climate change but about a planetary crisis — perhaps the most serious threat to humanity — as it includes high pollution levels and the number of premature deaths caused by it, as well as biodiversity loss and the disregard for nature.We are also facing consequences such as high migration rates, internal displacement, food insecurity, and we are in a moment when, in addition, elections are taking place in the United States, the outcome of which remains uncertain.